Review of Antiviral Effects of Glycyrrhiza glabra L. and Its Active Component, Glycyrrhizin - M Nassiri Asl; H Hosseinzadeh (Institue of Medicinal Plants, ACECR, 2007)
Background: Licorice (Glycyrrhiza sp.) belongs to family of Leguminosae. A number of components have been isolated from licorice, including triterpene saponins, flavonoids, isoflavonoides, chalcones and various other substances. Glycyrrhizic acid is the main biologically active component of it. Objective: The aim of this review is to provide an updated overview of experimental investigations focused on the antivirus effects of Glycyrrhiza and its active component, glycyrrhizin. Methods: A computerized search of published articles was performed using the electronic database such as MEDLINE from 1980 to 2005. Results: Glycyrrhiza exerts antiviral activity toward a number of viruses, including hepatitis A, B, C, varicella zoster, HIV, herpes simplex type-1, SARS, cytomegalo virus. Now glycyrrhizic acid has been used for the treatment of the patients with chronic active hepatitis and about the mechanism of glycyrrhizin's activity against other viruses, it seems that glycyrrhizin inhibits replication, affects cellular signaling pathways, upregulate expression of inducible nitrous oxide synthase and production of nitrous oxide in macrophages. Conclusion: Thus, it seems that future clinical research is needed to define the possible use of licorice and it active component, glycyrrhizic acid as effective antivirus agents for treatment other viral infections.